RE-UNDERSTANDING INDONESIAN STUDENT MOBILITY: INTRICATE ENTANGLEMENTS OF IDENTITY FORMATION AND LANGUAGE LEARNING - Thoyib, Muhammmad Edy; Degaf, Agwin; Rofiq, Zainur; Al Humairoh, Jihan (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2025)
The impact of globalization on higher education, understood as the increasing interconnectedness of academic systems, student mobility, and the circulation of knowledge across borders, has shaped students’ experiences of Studying Abroad (henceforth SA) and influenced their identity formation. This study explores the aspirations and challenges of the alumni of the student mobility program held by the Ministry of Religious Affairs (MORA) called MORA Overseas Student Mobility Awards (MOSMA), focusing on how they navigate identity in diverse cultural and linguistic settings throughout their SA journeys. Utilizing a narrative inquiry approach with a qualitative orientation, the research draws on Darvin and Norton’s model of language, identity, and investment. The data were collected through semi-structured interviews with four Indonesian SA students from three Islamic universities in East Java, ensuring representation of diverse perspectives. Thematic analysis was conducted to identify their aspirations, struggles, and identity negotiations. Results indicate that SA supports the acquisition of cultural, social, and linguistic capital but requires negotiation of identities when facing insecurities related to language use and integration into foreign cultures. The interplay between language learning and identity formation is complex, often shaped by unequal power relations in these contexts. Upon return, the students also participated in additional identity negotiations as they reconciled the SA-transformed self with pre-SA roles, synthesizing global experiences not consistently valued in home settings.